APPLICATION OF SETS-BASED WORKSHEETS (SCIENCE, ENVIRONMENT, TECHNOLOGY, SOCIETY) TO DEVELOP CRITICAL THINKING ABILITIES IN COLLOID MATERIALS - Salsa Virginia; Cucu Zenab Subarkah; Saepudin Rahmatullah (UIN Sunan Gunung Djati Bandung, 2021)
The purpose of this study was to analyze the increase in students' critical thinking skills after implementing SETS-based worksheets (science, environment, technology, society) on colloid material. In this study, the method chosen was pre-experiment and the research design used was a one-group pretest-posttest design which was carried out without a comparison group. The research subjects were 37 fourth semester students. The instruments used were worksheets and an eight-item essay test. The results show that the n-gain value obtained is 0.41, including the medium category. Indicators of critical thinking skills that have the highest value are identifying assumptions (79.05) and the lowest asking and answering indicators (28.37). Thus, SETS-based LK has an effect on the critical thinking skills of students.